The genomic landscape of oesophagogastric junctional adenocarcinoma. Issue 3 (9th October 2013) - Chong, Irene Y; Cunningham, David; Barber, Louise J; Campbell, James; Chen, Lina; Kozarewa, Iwanka; Fenwick, Kerry; Assiotis, Ioannis; Guettler, Sebastian; Garcia‐Murillas, Isaac; Awan, Saima; Lambros, Maryou; et al.
Abstract The incidence of oesophagogastric junctional (OGJ) adenocarcinoma is rising rapidly in western countries, in contrast to the declining frequency of distal gastric carcinoma. Treatment options for adenocarcinomas involving the oesophagogastric junction are limited and the overall prognosis is extremely poor. To determine the genomic landscape of OGJ adenocarcinoma, exomes of eight tumours and matched germline DNA were subjected to massively parallel DNA sequencing. Microsatellite instability was observed in three tumours which coincided with an elevated number of somatic mutations. In total, 117 genes were identified that had predicted coding alterations in more than one tumour. Potentially actionable coding mutations were identified in 67 of these genes, including those in CR2, HGF, FGFR4, and ESRRB. Twenty‐nine genes harbouring somatic coding mutations and copy number changes in the MSS OGJ dataset are also known to be altered with similar predicted functional consequence in other tumour types. Compared with the published mutational profile of gastric cancers, 49% (57/117) of recurrently mutated genes were unique to OGJ tumours. TP53, SYNE1, and ARID1A were amongst the most frequently mutated genes in a larger OGJ cohort. Our study provides an insight into the mutational landscape of OGJ adenocarcinomas and confirms that this is a highly mutated and heterogeneous disease. Furthermore, we have uncovered somatic mutations in therapeutically relevant genes which may represent candidate drug targets. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.